Perlindungan Hukum Terhadap Nasabah Koperasi Baitul Maal Wat Tamwil (BMT) Tidak Sehat di Kota Yogyakarta - Nurbaiti Prastyananda Yuwono, Nurbaiti Prastyananda Yuwono (Jurnal Hukum Islam, 2020)
This study aims to analyze the causes and effects of the unwell BMT cooperatives and legal protection for customers from the cooperatives. This empirical juridical research uses an integrated approach. Primary data were obtained from interviews and secondary data were obtained by searching primary and secondary legal materials. The technique of the analysis uses interactive models and analytical prescriptive. The results showed that the causes of BMT cooperatives in the city of Yogyakarta which were declared unwell, namely: 1) the lack of knowledge of management and managers about sharia financial management; 2) non- compliance with sharia principles; 3) limited capital; 4) non-performing loans; 5) professionalism of human resources; 6) not reporting financials; 7) not audited by a public accountant; 8) lack of managerial authority; 9) manager status is unclear; 10) legal issues; 11) basic BMT operational policies; 12) weak IT system. These conditions have an impact on the institution, management, managers and members and customers. Legal protection for customers is that if BMT cooperatives are declared unwell, the customers can use certain articles in the Cooperatives Act; Government Regulation Number 9 of 1995; Consumer Protection Act and; Civil Code. Legal protection is practically carried out through litigation and non-litigation. Therefore, there should be more intense supervision of unwell BMT cooperatives, including a commitment to immediately revise the Cooperative Act and the law on deposit insurance institutions for cooperatives.